Asymmetric repair of UV damage in nucleosomes imposes a DNA strand polarity on somatic mutations in skin cancer - Mao, Peng; Smerdon, Michael J.; Roberts, Steven A.; Wyrick, John J.

(untitled) (Genome Research, 2020)
Nucleosomes inhibit excision repair of DNA damage caused by ultraviolet (UV) light, and it has been generally assumed that repair inhibition is equivalent on both sides of the nucleosome dyad. Here, we use genome-wide repair data to show that repair of UV damage in nucleosomes is asymmetric. In yeast, nucleosomes inhibit nucleotide excision repair (NER) of the nontranscribed strand (NTS) of genes in an asymmetric manner, with faster repair of UV damage occurring on the 5′ side of the nucleosomal DNA. Analysis of genomic repair data from UV-irradiated human cells indicates that NER activity along the NTS is also elevated on the 5′ side of nucleosomes, consistent with the repair asymmetry observed in yeast nucleosomes. Among intergenic nucleosomes, repair activity is elevated on the 5′ side of both DNA strands. The distribution of somatic mutations in nucleosomes shows the opposite asymmetry in NER-proficient skin cancers, but not in NER-deficient cancers, indicating that asymmetric repair of nucleosomal DNA imposes a strand polarity on UV mutagenesis. Somatic mutations are enriched on the relatively slow-repairing 3′ side of the nucleosomal DNA, particularly at positions where the DNA minor groove faces away from the histone octamer. Asymmetric repair and mutagenesis are likely caused by differential accessibility of the nucleosomal DNA, a consequence of its left-handed wrapping around the histone octamer.